(untitled) (International Journal of Built Environment and Sustainability, 2022)
Rapid urbanization has transformed the pattern of urban land use to focus more on housing development. Unfortunately, the focus is less on improving the optimal use of community and green infrastructure (GI) facilities for communities in low-cost housing. Studies have shown that the lack of proper facilities and GI have impacted the individual, physical, psychological, and social health of a community. The outdoor facilities of low-cost housing developments are claimed to be very limited. Hence, the planning standards and guidelines for housing should go beyond their basic provisions, to offer a more conducive environment that improves the health and wellbeing of the community, especially in the event of a pandemic. Hence, the paper presents the preference of GI facilities in three low-cost strata housing flats in Selangor (Lembah Jaya, Kajang Utama, and PKNS PJS2 low-cost flats). The data collection consists of (a) spatial analysis using drone images that were converted into AutoCAD spatial maps; (b) interviews with the Joint Management Bodies; and (c) a questionnaire survey of residents (Lembah Jaya–n=116; Kajang Utama Flats–n=50; PKNS PJS2–n=85). The results reveal the limitations of the existing developments, challenges, and needs of the community. Considering the current COVID-19 pandemic, the outdoor spaces in the housing areas are indispensable for residents to relax their minds and do various allowable outdoor activities. This paper emphasizes that the provision of a new model for community and GI facilities in low-cost apartments is a must. A comfortable living environment in the area will support the ecological and social system of a community, thus promoting a good society. It urges the government, developers, and local governments to change the development approach for this type of housing to one that emphasizes a healthier, higher-quality, and more sustainable environment for the local community